The role of stock markets in promoting economic growth in Malaysia: Islamic vis-à-vis conventional - Abduh, Muhamad; Sukmana, Raditya (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga Yogyakarta, 2013)
The purpose of this study is to evaluate the dynamic effects of both Islamic and conventional stock markets development on the economic growth, particularly in Malaysia. The model estimation used to explain the relationship is the autoregressive distributed lag model with the variable of FTSE BM Emas Shariah Index to represent Islamic securities and FTSE BM Composite Index to represent the conventional. The data coverage is from Q1:2000 to Q4:2011. The result shows that there is no evidence of co-integration between the conventional markets and economic growth while there is a co-integration found between Islamic markets and economic growth. Moreover, the relationship between the development of the Islamic stock markets and economic growth occurs to be bidirectional.